Exploring the cultural use of indigenous healing cosmologies in the management of historical and intergenerational trauma amongst the Xhosa-speaking people of South Africa - May, Thandokazi Queeny (https://orcid.org/0000-0003-4665-6163) (Rhodes University, 2026)
Research on the trauma experienced by indigenous populations that have undergone colonization has found that colonialism has had a devastating effect on the wellbeing of these indigenous people in both historical and present-day contexts. This thesis aimed to identify the indigenous healing cosmologies used in the management of trauma by Xhosa-speaking people, who are a South African indigenous group that has historically experienced colonialism. This research engaged historical trauma (HT) theory and intergenerational trauma (IGT) theory, based on the premise that populations historically subjected to long-term, mass trauma such as colonialism, war and genocide exhibit a higher prevalence of disease and mental distress even several generations after the original trauma occurred. The psychological and emotional consequences of the initial trauma experience are transmitted inter-generationally with subsequent generations experiencing vicarious traumatization through the collective memory of the population. Data-gathering methods included extended participant observation within the community, alongside autoethnographic reflection on my own position as a Xhosa-speaking indigenous healer and community member. Extended interviews also took place with a wider network of traditional healers in the Eastern Cape, who also work with communities in the study area. In addition, I drew on methodologies which utilize dreaming and engagement with ancestral entities as a keyway of ‘coming to know’ in alignment with indigenous knowledge systems in this region. This study found that Xhosa-speaking people manage trauma by utilising various strategies including dreaming and spirituality to regain the balance of relationships that have been undermined by trauma. This approach is based on the indigenous Xhosa health model that defines health as a state of balanced relationships between the self, family, community, ancestors and environment. When these relationships are compromised, illness results. This finding aligns with that of Ward (2023) who found that indigenous dreaming and spirituality brings healing, greater resilience, and has the power to heal trauma. This study found that spiritual knowledge in Xhosa communities is used as a methodology for understanding humanity (Ubuntu) and maintaining balanced relationships thereby maintaining health. However, there are significant barriers to resolving historical and intergenerational trauma within Xhosa communities due to the magnitude of social disruption that has occurred and the impact these disruptions have had on indigenous healing modalities. This thesis proposes the concept that Ubuntu can be utilized as a strategy for managing trauma, through the adoption of the Xhosa indigenous health model that places emphasis on indigenous approaches to gathering knowledge that are supported by teachings from the ancestors. Amongst indigenous communities, trauma is experienced collectively, hence healing trauma and lifting the burden of disease caused by traumatization requires collective consciousness that is grounded in indigenous cosmologies.
Keywords: Generational trauma (http://id.loc.gov/authorities/subjects/sh2022006359); Ethnoscience (http://id.loc.gov/authorities/subjects/sh96010624); Traditional medicine (http://id.loc.gov/authorities/subjects/sh85083164); Anthropology; Historical trauma (https://www.wikidata.org/wiki/Q17030017); Traditional knowledge (https://www.wikidata.org/wiki/Q1428168); Xhosa (African people) (http://id.loc.gov/authorities/subjects/sh85148819)